Violence in College Students' Dating Relationships - Jordan-Berry, Carol E. (1984)
In a survey of 504 college students examining predictors of violence in heterosexual relationships, over half of both men and women had committed at least one physically violent act. Modest associations between physical violence and sexual aggression were uncovered. In a series of discriminant analyses, men who abused their partners were not readily distinguished from men who did not, but tended to by young, low in family income, traditional in attitudes toward women, abused as children, currently living with a women, and from Appalachian areas